Fungos endofíticos e epifíticos associados às folhas de cacaueiro - Moreira, Renata Lamos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Cocoa production in Brazil was drastically affected by the Witch's broom disease caused by the fungus Moniliophthora perniciosa. Previous studies showed that the microbiota associated with cocoa plants represent a possible barrier for the establishment of this parasite. However, little is known regarding the microorganisms associated with cocoa plants. In this sense we evaluated the diversity and composition of epiphytic and endophytic fungi associated with cocoa leaves in two farms. Based on a collection of fungi obtained in previous studies, the isolates were grown and grouped according to colony morphology. After morphtyping, representative isolates of each morphospecies were identified by sequencing the ITS region. After identification, fungal communities were characterized using ecological metrics. A total of 79 filamentous fungi were examined (40 endophytic and 39 epiphytic) comprising 12 genera and 25 species. Fusarium (33%), Bionectria (16.5%) and Pestalotiopsis (12.7%) were the prevalent genera. Acremonium sp. 1, Bionectria ochroleuca, Fusarium solani and Fusarium sp. 2 were found in both epiphytic and endophytic fungal communities. The epiphytic genera found in this study were also reported as endophytes in other reports, attesting for the commonness of such fungi. The diversity indices suggest that the epiphytic fungal community were more diverse in relation to the endophytic community. In addition, we found that cocoa plants from different farms share more endophytic than epiphytic taxa, suggesting that environmental factors help to determine the communities of fungi found on the leaf surface. This observation constitutes evidence that endophytic fungi may play a role for the host. In this sense, further studies are necessary to assess the putative defensive role of these fungi for cocoa plants against M. perniciosa

A produção de cacau no Brasil foi afetada drasticamente pela doença conhecida como vassoura-de-bruxa, cujo agente etiológico é o fungo Moniliophthora perniciosa. Estudos prévios sugerem que a microbiota associada ao cacaueiro representa uma possível barreira para o estabelecimento do parasita. Entretanto, pouco se conhece sobre os micro-organismos associados a essa planta. Nesse sentido, nós avaliamos a diversidade e composição de fungos epifíticos e endofíticos associados às folhas de cacaueiros em duas fazendas. Utilizando uma coleção de fungos obtida em estudos prévios, os isolados foram reativados e agrupados segundo as características morfológicas das colônias. Após a triagem morfológica, os isolados representativos de cada morfoespécie foram identificados utilizando sequências da região ITS. Após a identificação dos isolados, as comunidades de fungos foram caracterizadas utilizando métricas ecológicas. No total, foram avaliados 79 fungos filamentosos (40 endofíticos e 39 epifíticos) compreendendo 12 gêneros e 25 espécies. Fusarium (33%), Bionectria (16,5%) e Pestalotiopsis (12,7%) foram os gêneros mais abundantes, sendo que os fungos Acremonium sp. 1, Bionectria ochroleuca, Fusarium solani e Fusarium sp. 2 foram encontrados nas comunidades de fungos epifíticos e endofíticos. No geral, os gêneros de fungos encontrados como epifíticos nesse trabalho também foram reportados como endofíticos em outros estudos, o que indica o caráter ubíquo desses táxons. Os índices de diversidade sugerem que a comunidade de fungos epifíticos é mais diversa, quando comparada à comunidade de fungos endofíticos. Adicionalmente, observamos que cacaueiros localizados em diferentes fazendas tendem a compartilhar mais táxons endofíticos, em relação aos táxons epifíticos, o que sugere a influência de fatores ambientais na determinação das comunidades de fungos encontradas nas superfícies das folhas do cacaueiro...
Keywords: Fungos; Cacaueiro; Microbiota; Pragas - Controle